2012
DOI: 10.1103/physrevb.86.140506
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of count rate on magnetic field in superconducting thin-film TaN single-photon detectors

Abstract: We have studied the magnetic-field dependence of both dark-count rates and photon-count rates in a superconducting nanowire single-photon detector made of TaN in external magnetic fields |µ 0 H| < 10 mT perpendicular to the plane of the underlying meander structure and at T = 4 K.The dark-count rates show a characteristic field-dependence, which is asymmetric with respect to magnetic field direction. The field-and the current dependence of the dark counts can be quantitatively well explained if one assumes tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 25 publications
10
40
0
Order By: Relevance
“…This functional dependence of the dark-count rate R DC has been confirmed in TaN and NbN SNSPD up to ∼ 100 mT [61,67], as shown in figure 4(b). Furthermore, these studies have found evidence that the dark counts originate in the turnarounds of the meander structure.…”
Section: Dark Countssupporting
confidence: 66%
See 1 more Smart Citation
“…This functional dependence of the dark-count rate R DC has been confirmed in TaN and NbN SNSPD up to ∼ 100 mT [61,67], as shown in figure 4(b). Furthermore, these studies have found evidence that the dark counts originate in the turnarounds of the meander structure.…”
Section: Dark Countssupporting
confidence: 66%
“…This behaviour can be understood and modelled assuming one turn-around with a reduced critical current, symbolized by the red section of the schematic inset. A detailed discussion can be found in [61].…”
Section: Dark Countsmentioning
confidence: 99%
“…This theory predicts an exponential increase of count rate as a function of applied field, at constant bias current. As in the previous experiments, 13,15 we find that the rate of exponential increase predicted by this theory is an order of magnitude away from the experimental value.…”
supporting
confidence: 69%
“…Except near the ends of the straight sections of the superconducting meander the current density in the undisturbed equilibrium situation is homogeneous due to the fact that the strip width w ( K ¼ 2k 2 GL =d, where K is the effective 2D magnetic penetration depth, k GL ) d is the corresponding Ginzburg-Landau (GL) magnetic penetration depth in the bulk material and d the film thickness. Due to a current-crowding effect the current density in the 180 turnarounds of the meander structure is no longer homogeneous 27 and dark-count events most likely originate near these turnarounds, 28 but may be reduced by a more sophisticated meander design. 29 Despite this remarkable progress in understanding and optimization of SNSPD, some open questions remain, particularly in connection with the mechanism that is responsible for triggering the initial resistive cross-section.…”
Section: Introductionmentioning
confidence: 99%